Gas transport and storage capacity in shale gas reservoirs – A review. Part A: Transport processes. (December 2015) - Gensterblum, Yves; Ghanizadeh, Amin; Cuss, Robert J.; Amann-Hildenbrand, Alexandra; Krooss, Bernhard M.; Clarkson, Christopher R.; Harrington, John F.; Zoback, Mark D.
Abstract: For decades, scientists and engineers have been investigating and describing storage and transport mechanisms in geological porous media such as reservoir rocks. This effort has resulted in the development of concepts such as single-phase and multi-phase flow, which describe the storage and transport of fluids in conventional reservoir rock types such as sandstones and carbonates. However, many of these concepts are not directly applicable to unconventional reservoirs. For example, shale gas reservoirs consist of organic-rich lithotypes, which have high compressibility, very small pore throats, low porosities and extremely low and anisotropic permeabilities, and relatively low gas storage capacities. The models developed to describe conventional reservoirs do not accurately describe the hydrocarbon transport processes involved in these rocks. In this part A of the review paper, we aim to provide a concise and complete review on characterizing the fluid transport processes in unconventional reservoirs. We will examine processes occurring at various spatial scales, ranging from fracture flow on the centimeter scale down to slip-flow on the nanometer scale. Due to the softer nature of tight shales, many processes, such as slip-flow and the pore-throat compressibility, will have to be considered as coupled. We also develop a detailed description of the coupling between slip-flow, which is a fluid dynamic effect, and the pore-throat compressibility, which is a poroelastic effect, in unconventional reservoirs, and interpret experimental observations in light of this description. Furthermore, we discuss in detail how these transport properties depend on organic content, clay content and type, amount of pre-adsorbed water and pore compressibility.